REWARD AND PUNISHMENT IN ONLINE LEARNING PJOK OF THE COVID-19 PANDEMIC ON STUDENTS OF KARANGWINONGAN STATE SCHOOL, MOJOAGUNG - Eko Putut Dumiyanto; Galang Baqiyudin; M. Arfin Basri (Widyagogik, 2021)
The purpose of this study was to determine the impact of rewards and punishments on physical education learning during the online Covid-19 pandemic for students at SDN Karangwinongan Mojoagung. The method used in this study is a survey method using a questionnaire or questionnaire. The study uses a questionnaire that has been filled out by 40 respondents . This data collection technique using a questionnaire is used to determine the impact of giving rewards and punishments in learning PJOK online during the Covid-19 Pandemic. Based on the description of the research data above, it shows that the impact of Reward and Punishment on physical education learning during the online Covid-19 pandemic is in the moderate category. The highest frequency is 29 students with a percentage of 39.3% in the medium category. The impact of Reward and Punishment in physical education learning during the Covid-19 pandemic, which was in the high category of 17.6% or 3 students, medium category 54.3% or 29 students, low category 28.3% or 8 students.